IMMUNOMODULATORY EFFECTS OF ETHANOL IN BROILERS - M. Sajid; I.A. Khan; S. Ali; N. Akhtar (Journal of Animal and Plant Sciences, 2007)
An experiment of three week duration was conducted to study the effects of ethanol through crop tube on lymphoid organs and immune system in broilers. A total of ninety 21-days old broiler chicks were divided in to five equal groups (A to E). Groups A, B and C were given 40% ethanol 6ml, 4ml and 2ml respectively. The group D was kept as positive control given 6ml tap water through crop tube and group E was negative control. Ethanol through crop tube was given from day 21 to 42 days of age, continuously for three weeks. All groups were vaccinated against Newcastle Disease (ND) and Infectious Bursal Disease (IBD) and 3% sheep red blood cells were injected intravenously. At the end of each week, six birds were randomly selected and sacrificed. Blood samples were collected and serum was separated. Serum antibodies titers against New Castle Disease, Infectious Bursal Disease and sheep red blood cells were determined. Cell mediated immune response against the mallein antigen was also determined. No gross abnormality was observed in all lymphoid organs in treated groups as compared with controls. Relative weights of Bursa of Fabricus was non-significantly different in treated and non treated groups while relative weight of spleen and thymus were significantly (p<0.05) higher in treated groups as compared with control groups. Histopathological studies revealed decreased cellular density in spleen and thymus and decreased follicular diameter and epithelial height in Bursa of Fabricus in treated groups as compared with controls. The Geo mean titer (GMT) against ND, IBD and washed sheep RBCs was lowered in treated groups as compared with controls.
Keywords: Ethanol; Broiler; Histopathology; Immunity